KONTRIBUSI KECEPATAN TUNGKAI, KECEPATAN REAKSI LENGAN, POWER TUNGKAI, DAN POWER LENGAN TERHADAP KECEPATAN TEKNIK PUKULAN GYAKU TSUKI PADA ATLET PUTRI DI DOJO JAGABAYA RAHARJA - Aprilia, Mika; Candra Kurniawan; Suwarli; Fransiskus Nurseto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the contribution of leg speed, arm reaction speed, leg power, and arm power to the speed of the Gyaku Tsuki punching technique in female athletes at Jagabaya Raharja Dojo. The research employed a descriptive method with a correlational approach. The sample consisted of 20 female athletes selected using a total sampling technique. The research instruments included tests of leg speed, arm reaction speed, leg power, arm power, and Gyaku Tsuki punching speed. Data analysis was conducted using Pearson Product Moment correlation to examine partial relationships, as well as multiple correlation with the F-test to analyze simultaneous relationships at a significance level of 0.05. The results showed that leg speed had a significant relationship with the speed of the Gyaku Tsuki punch (r = 0.749). Arm reaction speed demonstrated a very strong and significant relationship (r = 0.896). Leg power also showed a significant relationship (r = 0.609), while arm power had a strong and significant relationship (r = 0.722). Simultaneously, leg speed, arm reaction speed, leg power, and arm power were significantly related to the speed of the Gyaku Tsuki technique, with a multiple correlation value of R = 0.933 and a contribution of 87%. These findings indicate that all research hypotheses were accepted, and these biomotor components should be developed in an integrated manner to improve the speed of the Gyaku Tsuki technique in karate athletes.